Post-translational modifications of voltage-gated sodium channels in chronic pain syndromes - Laedermann, Cedric J.; Abriel, Hugues; Decosterd, Isabelle (Frontiers in Pharmacology, 2015)
In the peripheral sensory nervous system the neuronal expression of voltage-gated sodium channels (Navs) is very important for the transmission of nociceptive information since they give rise to the upstroke of the action potential (AP). Navs are composed of nine different isoforms with distinct biophysical properties. Studying the mutations associated with the increase or absence of pain sensitivity in humans, as well as other expression studies, have highlighted Nav1.7, Nav1.8, and Nav1.9 as being the most important contributors to the control of nociceptive neuronal electrogenesis. Modulating their expression and/or function can impact the shape of the AP and consequently modify nociceptive transmission, a process that is observed in persistent pain conditions. Post-translational modification (PTM) of Navs is a well-known process that modifies their expression and function. In chronic pain syndromes, the release of inflammatory molecules into the direct environment of dorsal root ganglia (DRG) sensory neurons leads to an abnormal activation of enzymes that induce Navs PTM. The addition of small molecules, i.e., peptides, phosphoryl groups, ubiquitin moieties and/or carbohydrates, can modify the function of Navs in two different ways: via direct physical interference with Nav gating, or via the control of Nav trafficking. Both mechanisms have a profound impact on neuronal excitability. In this review we will discuss the role of Protein Kinase A, B, and C, Mitogen Activated Protein Kinases and Ca++/Calmodulin-dependent Kinase II in peripheral chronic pain syndromes. We will also discuss more recent findings that the ubiquitination of Nav1.7 by Nedd4-2 and the effect of methylglyoxal on Nav1.8 are also implicated in the development of experimental neuropathic pain. We will address the potential roles of other PTMs in chronic pain and highlight the need for further investigation of PTMs of Navs in order to develop new pharmacological tools to alleviate pain.